2022
DOI: 10.3389/fpsyg.2022.962403
|View full text |Cite
|
Sign up to set email alerts
|

A model of abusive supervision, self-efficacy, and work engagement among Chinese registered nurses: The mediating role of self-efficacy

Abstract: Abusive supervision could negatively influence individual work attitudes, behaviors, and work outcomes. Self-efficacy and work engagement can help to increase nursing performance. But few studies have attempted to determine the specific mechanism between them in China. The objective is to analyze the levels of abusive supervision, self-efficacy, and work engagement, and to explore the relationship between these three variables among Chinese clinical registered nurses. A predictive, cross-sectional quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…As evidenced by previous research studies, this article is unique and provides new insights regarding the role of supervisor support, work engagement, and self‐efficacy, particularly in the cultural context of Pakistan. The findings of this study are consistent with prior studies of Xu et al (2022), Sun et al (2022), Rabiul et al (2022) and Uppathampracha and Liu (2022).…”
Section: Discussionsupporting
confidence: 93%
“…As evidenced by previous research studies, this article is unique and provides new insights regarding the role of supervisor support, work engagement, and self‐efficacy, particularly in the cultural context of Pakistan. The findings of this study are consistent with prior studies of Xu et al (2022), Sun et al (2022), Rabiul et al (2022) and Uppathampracha and Liu (2022).…”
Section: Discussionsupporting
confidence: 93%
“…Among them, two studies reported a significant decrease in moral courage among nurses who worked with abusive nurse managers. 34,41 Sun et al 46 demonstrated a significant negative influence of abusive supervision on nurses’ self-efficacy, while Mostaf 41 reported a negative effect of abusive supervision on nurses’ moral efficacy. However, one study found no effect of abusive supervision on role ambiguity.…”
Section: Resultsmentioning
confidence: 99%
“…Job satisfaction Ng et al 43 Significantly decreased Pyc et al 40 Significantly decreased Rodwell et al 45 Significantly decreased Sharif Nia et al 29 Significantly decreased 3. Work engagement Sun et al 46 Significantly decreased Osei et al 38 Significantly decreased 4. Public service motivation Ng et al 43 No change Behavior or performance-based outcomes 5.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, this study indicates that core selfevaluation is an independent predictor of nurses' work engagement. Several studies have demonstrated that a strong sense of self-efcacy (often described as a component of core self-evaluation) can help nurses continue to engage in clinical practice when they experience job stress and problems [7,43]. Important information about the role of core selfevaluation in explaining work engagement among nurses needs to be included, as earlier studies almost focused on job satisfaction [44].…”
Section: Discussionmentioning
confidence: 99%